Application of Visual Psychology in Personalized Sports Industrial Design - Zhou Yue, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This research investigates the application of visual psychology to the industrial design of personalized sports equipment. Based on the development of customized sports art fitness public service products, this study analyzed the physiological and visual psychological characteristics of children, adolescents, middle-aged, and elderly individuals at different age stages. 100 questionnaires were disseminated to fitness enthusiasts for this study, and 92 were returned for a recovery rate of 92%. The findings of this study indicate that public service products of sports art fitness should be designed with diverse age groups in mind. Based on the empirical evidence, the findings of this study are novel. Additionally, this research has both theoretical and practical implications. To improve the corpus of knowledge pertaining to students' psychological well-being, scholars should follow the future directions of this research in future investigations.